(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1990)
The PC/33b well drilled by the ENEL Company in the Monte Amiata area near Piancastagnaio (Southern Tuscany, Italy) yielded some fossiliferous layers from 3024.40 to 3028.40 m. Thc cored interval is interpreted as belonging to the Paleozoic Basement of the Tuscan Series which includes some informai Units (A, Band C) indicated as "Formations" in this paper. "Fm" A consists of graphitic phyllites and metasandstones with rare intercalations of mudstone to wackestone-packstone; "Fm" B consists of chloritic phyllites and metasandstones with some intercalations of impure microcrystalline dolostones. "Fm" A seems to pass to the underlying "Fm" C, which gradually consists of thick mudstone to dolostone layers interbedded into the graphitic metasandstone-phyllitic lithotypes. The few crystalline fossiliferous layers occur in the transition levels between "Fm" A and "Fm" C. The fossils identified in the cored interval belong to fragmented crinoids, gasteropods, gymnocodiacean and dasycladacean algae, and to foraminifers (mainly fusulinids). Despite the strong recrystallization and metamorphism affecting the rocks, some fusulinids could be identified. They are Praeparafusulina cf. lutugini (Schellwien) (possibly reworked), Polydiexodina (Eopolydiexodina ?) cf. shabalkini Leven, Yangkienia sp., Y. aff. compressa (Ozawa), Cancellina sp., Pseudodoliolina "ex. gr." P. ozawai Yabe & Hanzawa,? Chusenella sp., ghosts of Misellina sp. and ?Neofusulinella sp. This fusulinid association is indicative of the Cancellina Zone of Kubergandian age (Late Permian), which is recorded in Italy for the first time. A brief review of the Permian fusulinid assemblages from the Apennine region is included in the conclusions.